Peningkatan Kualitas Lingkungan Melalui Pelatihan Pengolahan Limbah Rumah Tangga kepada Ibu-Ibu PKK Gondosari - Satya Budi Nugraha; Rini Setyo Witiastuti; Eta Yuni Lestari (CV. Multi Kreasi Media, 2024)
The Gondosari area, located in the Susukan Subdistrict, Ungaran Timur District, Semarang Regency, faces issues in managing household waste, specifically used cooking oil and food scraps (fruits/vegetables). The accumulation of waste at Temporary Waste Disposal Sites (TPSS) leads to foul odors and creates an unpleasant environment and scenery. This community service activity aims to provide training to residents (particularly members of the PKK women's group) in the Gondosari area to enhance their knowledge and understanding of household waste management (used cooking oil and fruit/vegetable scraps). The methods applied include training on making eco-enzymes from fruit scraps, as well as processing used cooking oil into soap and candles. The outcome of the training is an increase in knowledge and skills among the PKK women's group in managing their household waste.